Clustering Regency/City in Indonesia based on Human Development Index Indicators - Nurhasanah Nurhasanah; Nany Salwa; Lyra Ornila (Proceedings of AICS - Social Sciences, 2017)
Human Development Index (HDI) is an index that measures the success rate of human development in a region. Development undertaken by the government aims to create a prosperous and peaceful society. The problems that often arise in the development process are the uneven development in every regency/city in Indonesia. This can be seen from the value of HDI is still different in each regency/city in Indonesia. The purpose of this study is to categorize regency/cities in Indonesia based on indicators of HDI. The clustering method is K-means cluster analysis. The data used is the data indicator HDI Indonesia 2015 obtained from BPS website every province. The results of the analysis formed 4 clusters. The first cluster consisted of 20 regency with average HDI indicator is very low, the second cluster consisted of 148 regency/city with average HDI indicator is medium, the third cluster consisted of 88 regency/city with average HDI indicator is very high, and the fourth cluster consists of 258 regency/city with HDI indicators is very high.